Simulation of Landsman Converter with Npc-Multilevel Inverter for Water Pump Applications - Gagana R. Nayak,; S. Pradeepa, (Journal of Power Electronics and Devices, 2019)
This study explains the operation and design of Landsman DC-DC converter employing maximum power point tracking (MPPT) controller for maximum power conversion in a solar Photovoltaic (PV) array. The output DC voltage of converter through inverter is fed to the induction motor based water pump. The above system is proposed by using a neutral point clamped (NPC) multilevel inverter for the DC to AC conversion. Incremental conductance algorithm is chosen to operate the PV array close to optimum operating point. The input voltage and current is sensed to achieve MPP. Output voltage is sensed to get required regulated output voltage. The controller is designed to obtain the regulated output at different load and irradiance conditions. The overall proposed system is simulated and the THD analysis is done for the output voltage of the inverter.